Fabrication And Characterization Of Denture Adhesive Filled Starches Containing Antimicrobial Agents - Rozailan, Nai'mah (Universiti Sains Malaysia, 2018)
Nowadays, denture adhesive is widely used for denture wearers in order to improve the denture‘s retention, stability and function especially during mastication. Adhesiveness plays an important role in denture adhesive, to enhance retention and gives more psychological confidence for the patient. The objective of this study is to fabricate and characterize the denture adhesive filled starches and containing antimicrobial agents. Tapioca starch is chosen as filler as it has proven to exhibit excellent adhesiveness. Several studies have been reported essential oils such as Peppermint oil, Tea Tree oil (TTO) and Coconut Oil (CNO) have effectiveness against Candida albicans. Therefore, these essential oils were chosen in this research. There are several characterization and test were conducted such as Fourier Transform Infrared Spectroscopy (FTIR), Texture Profile Analysis (TPA), Tensile Bond Strength (TBD), Shear strength test, pH test, antimicrobial test and morphology study for Scanning Electron Microscopy (SEM), solubility and swelling test. Denture adhesive with 10% filler loading exhibits the optimum starch composition as it shows highest adhesiveness, shear strength and elongation at break. However, for tensile bond strength and hardness no significant trend is observed. Pure essential oils; Peppermint oil and Tea tree oil are proven to inhibit the bacterial growth, but Coconut oil does not show any zone of inhibition. Antimicrobial agents in denture adhesive also loss their activity due to low concentration or denture adhesive deactivate the reaction innate immune molecules in antimicrobial agents.